A novel functional group difference-based selective etching strategy for the synthesis of hollow organic silica nanospheres. Issue 32 (14th March 2016) - Zeng, Fanlong; Chen, Lianxi; Li, Jie; Ye, Xinshan; Yu, Huogen; Liu, Zhenhui
Abstract : CTES@TCPTES were synthesized by CTES and TCPTES, and then TC-HSNSs could be fabricated with the basic etching agent based on stability difference between core and shell. Abstract : A facile and effective "functional group difference-based selective etching" strategy has been developed to prepare organic functionalized hollow silica nanospheres (OHSNSs) with well-defined morphology and uniform size. The key point of the strategy is to introduce different organic groups into both core and shell for the purpose of changing their relative stability against etching, which results in the preferential etching of the organic functionalized inner core. In this paper, bifunctionalized core–shell silica nanospheres synthesized by using 2-cyanoethyltriethoxysilane (CTES) as the core and 3-thiocyanatopropyltriethoxysilane (TCPTES) as the shell can be easily transformed to thiocyanato group-functionalized hollow silica nanospheres (TC-HSNSs) in a Na2 CO3 solution, based on the stability difference between the cyano group functionalized inner core and the thiocyanato group functionalized outer shell. Transmission electron microscopy (TEM) confirms that the formation of TC-HSNSs undergoes the process of selectively etching the inner core. Moreover, Fourier transform infrared (FTIR), energy dispersive spectroscopy (EDS) and elemental analysis (EA) prove that only the thiocyanato group is observed in the final product. In addition, the application of TC-HSNSs in the adsorption of aspirin has also been investigated.